A STUDY OF THE RATE OF OBESITY IN ADULT FEMALE POPULATION OF HAZARA - Hussain, M.; Begum, Nazakat (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: One hundred adult, non-pregnant women were examined for various body parameters which determine the obesity. It was observed that 22% of the subjects under observation were obese on the whole. Moreover, it was noticed that the rate of obesity increased among the female subjects with the advancing age. The main reason for the obesity was found to be the intake of high calorie diet with lesser physical activities.